Zeleno zavajanje, plastična prihodnost - Murn Lindič, Žiga (Pravni letopis, 2025)
Plastic has become an integral part of modern life, yet its widespread use entails significant environmental and social consequences. To address these challenges, the European Union has established a comprehensive legal framework encompassing restrictions on single-use plastics, the promotion of recycling, and the transition to a circular economy, while actively engaging in the development of international legally binding initiatives. Greenwashing remains a pervasive issue, as environmental claims regarding products often misrepresent their recyclability or overall environmental impact. In response, the EU has enacted Directive (EU) 2024/825, proposed the Directive on Green Claims and adopted regulation 2025/40, which establish standards for the verification, communication, and substantiation of environmental claims as well as packaging requirements. Despite these measures, discrepancies persist between stated recyclability and actual recycling outcomes, undermining consumer protection. Analyses of everyday plastic use highlight the necessity of an integrated legal framework that aligns production, waste management, and oversight of environmental claims to achieve genuinely sustainable practices.
Keywords: circular economy; consumer protection; EU legal framework on plastics; green claims; greenwashing; krožno gospodarstvo; Plastične mase; plastika za enkratno uporabo; pravna ureditev plastike v EU; reciklabilnost; recyclability; single-use plastics; Varstvo okolja; Varstvo potrošnikov; zelene trditve; zeleno zavajanje